From affiliation to standardization: Bridging policy and practice through mentoring in an affiliated madrasah - Nur Mutima (Eduvista: Journal of Education and Innovation, 2026)
Learning standardization in madrasahs continues to face challenges because academic standards are often implemented without sustained mentoring, while studies examining mentoring as an integrative mechanism for learning standardization in affiliated madrasahs remain limited. This study aims to analyze the mentoring process implemented by Pondok Pesantren Sidogiri in establishing learning standardization at Madrasah Nurul Huda following its affiliation with MMU A-84. A qualitative case study design was employed using semi-structured interviews, non-participant observation, document analysis, and thematic analysis involving five purposively selected participants. The findings reveal that mentoring serves as the central mechanism integrating curriculum alignment, teaching practices, and academic supervision, resulting in more consistent learning standardization while simultaneously supporting student character development. This study contributes conceptually by proposing a mentoring model as an integrative mechanism for establishing learning standardization and offers practical implications for improving educational quality in Islamic educational institutions. Abstrak Standardisasi pembelajaran di madrasah masih menghadapi berbagai tantangan karena implementasi standar akademik sering kali belum didukung oleh mekanisme mentoring yang berkelanjutan. Sementara itu, kajian mengenai peran mentoring sebagai mekanisme integratif dalam mewujudkan standardisasi pembelajaran pada madrasah afiliasi masih relatif terbatas. Penelitian ini bertujuan untuk menganalisis proses mentoring yang diterapkan Pondok Pesantren Sidogiri dalam membangun standardisasi pembelajaran di Madrasah Nurul Huda setelah berafiliasi dengan MMU A-84. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus melalui wawancara semi-terstruktur, observasi nonpartisipan, dokumentasi, dan analisis tematik terhadap lima informan yang dipilih secara purposive. Hasil penelitian menunjukkan bahwa mentoring berperan sebagai mekanisme utama yang mengintegrasikan penyelarasan kurikulum, praktik pembelajaran, dan supervisi akademik sehingga menghasilkan standardisasi pembelajaran yang lebih konsisten sekaligus mendukung pengembangan karakter santri. Penelitian ini memberikan kontribusi konseptual dengan menawarkan model mentoring sebagai mekanisme integratif dalam membangun standardisasi pembelajaran serta memberikan implikasi praktis bagi pengembangan mutu pendidikan di lembaga pendidikan Islam.